The impact of magnetic fields on the chemical evolution of the supernova-driven ISM - Pardi, Anabele-Linda; Glover, Simon; Klessen, Ralf S. (Arxiv, 2016)
We present three-dimensional magneto-hydrodynamical simulations of the self-gravitating interstellar medium (ISM) in a periodic (256 pc)$^3$ box with a mean number density of 0.5 cm$^{-3}$. At a fixed supernova rate we investigate the multi-phase ISM structure, H$_{2}$ molecule formation and density-magnetic field scaling for varying initial magnetic field strengths (0, $6× 10^{-3}$, 0.3, 3 $μ$G). All magnetic runs saturate at mass weighted field strengths of $\sim$ 1 $-$ 3 $\m